IMPLEMENTASI PERAN BAGIAN HUMAS DAN PROTOKOL DALAM MEMBANGUN CITRA PEMERINTAH KABUPATEN MALUKU TENGAH - HALLATU, GREESYE YOSMA; UFI, JOSEP ANTONIUS (Patria Artha Management Journal, 2024)
The aims of this research is to understand how the role of the public relations andprotocol department in building the image of the Central Maluku RegencyGovernment is carried out and the factors that support and hinder it. Thisresearch is a qualitative type of research and the informants consist of people inthe community as well as public relations and protocol staff. Data were collectedthrough observation, interviews, and document collection. The data wereanalyzed using the qualitative analysis method, which involves the stages ofreduction, presentation, verification, and conclusion drawing.The PublicRelations Department has done its job well in building the image of the CentralMaluku Regency Government by performing the roles of expert advisor,facilitator, and problem solver. As expert advisors, PR employees carry out theirduties to use their abilities to solve problems faced by the organization and findsolutions to these problems. PR serves as a communicator or mediator whoprovides opportunities for the public to participate in the government process byexpressing their views. By being a problem solver, PR helps company leaders takeaction or make decisions in a professional and logical manner. The work of publicrelations and protocol departments in building the government's image issupported and hindered by communication, resources, disposition, andbureaucratic structure.